Primary care quality of primary healthcare institutions in china: current status and influencing factors - Kexin Zhan; Chuchuan Wan; Ennan Wang; Yuankai Huang (Archives of Public Health)
Abstract Objective This study aims to assess the current state of primary care quality within Primary Healthcare Institutions (PHIs) in China and analyze potential factors that may influence the quality of primary care provided. Methods Employing convenience sampling, this research utilized the Chinese Primary Care Assessment Tool (PCAT-C) to gather cross-sectional data on patients’ experiences with primary care during visits to PHIs across the country. A multivariate linear regression model was established to discuss the effects of various factors on the quality of primary care at PHIs. Results The study encompassed 2,063 valid cases, with an overall PCAT score of 71.31 (SD = 11). Among the different dimensions, the average score for the Comprehensiveness dimension was the highest at 77.78 ± 15.83, followed by Continuity (75.81 ± 10.68), Family-centered (75.67 ± 17.69), First Contact (69.46 ± 10.36), Coordination (69.39 ± 16.84), and the Community-orientation dimension with the lowest average score at 59.75 ± 16.93. The regression analysis (R2 = 0.0437, p < 0.000) indicated that the patient’s area(Eastern, Middle or Western) (p < 0.001), region(Urban or Rural)(p = 0.026), presence of adult children (p = 0.008), working status (p = 0.003), family annual income (p = 0.007), participation in commercial medical insurance (p = 0.001), seeking medical attention for illness was sought (p = 0.014), the number of hospital beds per 10,000 population (p = 0.007), and per capita health expenditure as a percentage of GDP per capita (p = 0.021) significantly impact the quality of primary care at PHIs. Conclusion The quality of primary care for PHIs in China is still low and is affected by both micro and macro factors. The quality of primary care at PHIs in China is still relatively low, particularly in the Community-orientation dimension. Apart from being influenced by microscopic factors, the quality of primary care at PHIs is also affected by macro factors such as overall health expenditure and economic status. It is recommended that efforts be made to enhance the equity of the medical and health resource allocation mechanism, thereby promoting balanced regional development.